Ebbs and Flows: A Longitudinal Study of an English Language Instructor's Motivation to Learn Korean. Issue 5 (3rd September 2018) - Gearing, Nigel; Roger, Peter
ABSTRACT: Native English speaking language teachers who live and work in various parts of the world often express a desire to learn the language of their host country. Without sustained levels of motivation, however, their desires are unlikely to be realized. This article reports the findings of a longitudinal case study of an American English language instructor working at a South Korean university. It examines the factors that impacted her motivation to learn Korean, and explores the ebbs and flows that characterized her motivation over a one-year period. Findings revealed that while the participant did express a desire to learn Korean and formulated learning goals, the action necessary to achieve these goals did not occur. This article draws on the L2 Motivational Self System and the Process Model of L2 Motivation to provide a dual theoretical perspective on the findings.